Effect of Fasting on Lipid Metabolism (1) - Nakamura, Atsuko; Ohtani, Yatsuho; Tezuka, Tomomichi; Innami, Satoshi; Nagayama, Sumiko (Eiyōgaku zasshi, 1971)
In this experiment, the effect of fasting period on the lipid metabolism was compared with the rats fed ad libitum (group A) and the rats fed on a limited diet (group B). In the restricted group, food intake was reduced gradually from 15g of first day to 6.5g immediately prior to sacrifice. After 15 days of feeding 6 rats of each subgroup were sacrificed by decapitation. Before decapitation animals were fasted for 1, 4, 10, 16, and 24 hours (Subgroup A1-A24 for ad libitum and B1-B24 for restricted). 5:00 A. M. was selected as the starting time of fasting for group A. 5:00 P. M. was the starting time of fasting for group B. In group A, as fasting time passed, liver weight decreased and the total lipid and fatty acid contents per gram liver increased. Almost no change was seen in liver fatty acid composition up to 16hrs. of fasting. But in 24 hours of fasting, the proportion in C18, and C20-4 to total fatty acid decreased, and the proportion in C18-2 increased. In serum of rats fed ad libitum, the proportion in C16, C16-1 and C20-4 increased, and the proportion in C18-2 decreased as the fasting proceeded. In group B, no difference was seen in liver weight, liver total lipid and total fatty acid as the fasting proceeded. Fatty acid composition of the liver also did not alter with fasting time. On the other hand, there was no change in serum total fatty acid content up to 16 hours of fasting but decreased thereafter. As described above, there was an essential difference of fatty acid metabolism during fasting between ad libitum feeding and restricted feeding. Therefore, fasting period before decapitation should be strictly considered especially in lipid experiment.